2008
DOI: 10.1111/j.1365-313x.2008.03419.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced activity of Arabidopsis thaliana HMT2, a methionine biosynthetic enzyme, increases seed methionine content

Abstract: In the S-methylmethionine cycle of plants, homocysteine methyltransferase (HMT) catalyzes the formation of two molecules of methionine from homocysteine and S-methylmethionine, and methionine methyltransferase (MMT) catalyzes the formation of methionine from S-methylmethionine using S-adenosylmethionine as a methyl group donor. Somewhat surprisingly, two independently isolated knockdown mutations of HMT2 (At3g63250), one of three Arabidopsis thaliana genes encoding homocysteine methyltransferase, increased fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 29 publications
3
55
1
Order By: Relevance
“…These results indicate that modifying catabolism has the potential to improve the nutritional quality of crop seeds and vegetative tissues. However, a variety of pleiotropic effects were seen for these examples, ranging from increased seed Cys in threonine aldolase1 mutants (Lu et al, 2008) to broader amino acid increases in Lys overproducing lines (Karchi et al, 1994;Zhu and Galili, 2003) and BCAA catabolic mutants (Gu et al, 2010;Lu et al, 2011;and this study), and defects in vegetative and seed development or seed viability (Zhu and Galili, 2004;Lee et al, 2008;Ding et al, 2012). It is not surprising that these relatively old processes are broadly connected and difficult to perturb without resultant undesirable effects (Milo and Last, 2012).…”
Section: Broader Implicationsmentioning
confidence: 66%
See 1 more Smart Citation
“…These results indicate that modifying catabolism has the potential to improve the nutritional quality of crop seeds and vegetative tissues. However, a variety of pleiotropic effects were seen for these examples, ranging from increased seed Cys in threonine aldolase1 mutants (Lu et al, 2008) to broader amino acid increases in Lys overproducing lines (Karchi et al, 1994;Zhu and Galili, 2003) and BCAA catabolic mutants (Gu et al, 2010;Lu et al, 2011;and this study), and defects in vegetative and seed development or seed viability (Zhu and Galili, 2004;Lee et al, 2008;Ding et al, 2012). It is not surprising that these relatively old processes are broadly connected and difficult to perturb without resultant undesirable effects (Milo and Last, 2012).…”
Section: Broader Implicationsmentioning
confidence: 66%
“…First, a growing body of evidence points to major roles of amino acid catabolism and interconversion in regulating levels of six of the nine free essential amino acids (Ile, Leu, Lys, Met, Thr, and Val) in seeds of a variety of plants (Karchi et al, 1994;Zhu and Galili, 2003;Jander et al, 2004;Joshi et al, 2006;Lee et al, 2008;Gu et al, 2010;Lu et al, 2011;Angelovici et al, 2013). These results indicate that modifying catabolism has the potential to improve the nutritional quality of crop seeds and vegetative tissues.…”
Section: Broader Implicationsmentioning
confidence: 99%
“…However, despite the efficient transport capability of SMM, Arabidopsis and maize mmt mutants, which are unable to synthesize SMM, grow and reproduce normally, suggesting a minimal regulatory role for SMM in sulfur transport of at least these two species (Kocsis et al, 2003). Notwithstanding, a recent report (Lee et al, 2008) showed that a mutant Arabidopsis plant overaccumulating Met in its seeds is due to a mutation eliminating the activity of HMT2, one of the three Arabidopsis HMT isozymes that recycle SMM into Met (Lee et al, 2008). The HMT2 gene is expressed in vegetative tissues where it apparently shifts the balance from Met to SMM in these source tissues.…”
Section: Improving Met Content By Genetic Engineeringmentioning
confidence: 98%
“…The enzymes homocysteine methyltransferase and methionine methyltransferase catalyze the interconversion of methionine and S-methylmethionine (Figure 8), a metabolic cycle that functions in phloem loading and amino transport (Bourgis et al, 1999;Lee et al, 2008). Whereas homocysteine methyltransferase forms two molecules of methionine from S-methylmethionine and homocysteine, methionine methyltransferase uses S-adenosylmethionine as a methyl group donor to form S-methylmethionine from methionine.…”
Section: The S-methylmethionine Cyclementioning
confidence: 99%